Feasibility study of Haffa Mini- hydropower plant in Bambasi Woreda - Biru, Abdu; Yahya, Aminat (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Nowadays; Ethiopia is one of the countries which is under developing and one of the strategies to be used to develop the country is to explore and develop the sector of energy in Ethiopia. Our country Ethiopia needs to develop the rural electrification sectors in order to provide illumination to the population living in those rural remote areas for rapid development in different sectors like schools; health centers; business centers and administrative officers. Hence the current energy regime in Ethiopia, that is heavily reliant on the burning of biomass, has had major implications for the environment. There is a fast depletion of renewable sources that was used in the past for the generation of electricity and the difficulty in reachability of the grid supply to the remote villages was a big challenge faced. The best possible remedial measure in this scenario is to make use of the natural resources available to generate electricity. In an endeavourance towards this end, the paper has been formulated for the electrification of six selected remote Kebeles in Bambasi woreda. This kebeles are kinds of locality in which there are a tribal settlement of about 600 families each that do not have privilege of electrical energy supply. The present work focus on the feasibility studies carried out at the site for the assessment of mini hydro power plant potential of the site. The results of the study reveal that there is a huge potential at the site to develop a mini hydro power plant which would meet the energy demand of the tribal settlement and thereby improving their living condition. But the river is intermittent so that it is recommended to construct dam for the purpose of storage of water.